2021
DOI: 10.1088/1757-899x/1115/1/012078
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antioxidant Activity of Hippobroma longiflora Extracts

Abstract: This study aims to identify the secondary metabolite compounds and to test the antioxidant activity of ethanol extract, n-hexane fraction, and chloroform fraction of Hippobroma longiflora leaves. Extraction was carried out by the maceration method using ethanol. The resulting crude ethanol extract was then partitioned with n-hexane and chloroform. Each extract and fraction was then tested by phytochemical screening. Antioxidant activity testing was carried out using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Haryoto et al, 33 Kitolod leaves extract showed cytotoxic activity with moderate ability on MCF-7 cells Martiningsih et al, 34 The antioxidant activity of the ethanol extract of kitolod leaves was more potent than the n-hexane and chloroform fractions, but smaller than ascorbic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Haryoto et al, 33 Kitolod leaves extract showed cytotoxic activity with moderate ability on MCF-7 cells Martiningsih et al, 34 The antioxidant activity of the ethanol extract of kitolod leaves was more potent than the n-hexane and chloroform fractions, but smaller than ascorbic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Hal tersebut memperlihatkan bahwa sebagian besar dari keberadaan kitolod sebagai gulma hanya dibuang sebagai limbah hasil penyiangan lahan sehingga pemanfaatannya dinilai belum optimal. Beragam penelitian telah mengkaji potensi dari kitolod yang meliputi adanya aktivitas antioksidan (Martiningsih et al, 2021), antibakteri (Simanjuntak, 2020), antikanker (Hapsari et al, 2016), hingga memiliki aktivitas tabir surya (Savira dan Iskandar, 2020). Aktivitas-aktivitas tersebut menunjukkan bahwa kitolod memiliki potensi yang sangat besar untuk dimanfaatkan secara optimal sebagai sumber tanaman penghasil senyawa polifenol.…”
Section: Pendahuluanunclassified
“…A total of 14 types of polyphenols compounds were identified in kitolod leaves and most of the compounds belong to flavonoid groups [5]. Kitolod leaves were known to have strong antioxidant activity and moderate anticancer activity against HeLa cells [6], [7]. Furthermore, strong antibacterial activities were provided by kitolod leaves against Staphylococcus aureus, Salmonella typhi, and Escherichia coli [8], [9].…”
Section: Introductionmentioning
confidence: 99%